2007
DOI: 10.1007/s11340-007-9034-z
|View full text |Cite
|
Sign up to set email alerts
|

Plated and Intact Femur Strains in Fracture Fixation Using Fiber Bragg Gratings and Strain Gauges

Abstract: This paper presents an experimental methodology to determine plated and intact femur strains using fiber Bragg gratings and strain gauges. A plated and an intact synthetic femur were used and loaded under a simplistic static load of 600 N. A stainless steel (316L) plate was used to fixate a simulated 45°fracture on one femur. Strains were recoded at the same sites on both femurs. Strain shielding is shown to be more pronounced at the distal region of the plated femur. The experimental methodology based on fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Strains were recorded at the same sites on both femurs and good linearity was found for different loads. As strain measurement on bone plates using SG is technically difficult and not feasible, FBGs are good alternative to assess the stiffness of callus formation of fractured bones [15].…”
Section: Biomechanicsmentioning
confidence: 99%
“…Strains were recorded at the same sites on both femurs and good linearity was found for different loads. As strain measurement on bone plates using SG is technically difficult and not feasible, FBGs are good alternative to assess the stiffness of callus formation of fractured bones [15].…”
Section: Biomechanicsmentioning
confidence: 99%
“…. Talaia et al (2007) have first reported use of FBG sensor array to study strains in fracture fixation of synthetic femur. As strain measurement on bone plates using ESG is technically difficult and not feasible, FBGs are good alternative to assess the stiffness of callus formation of fractured bones.…”
Section: Biomechanicsmentioning
confidence: 99%
“…For example, one work described the properties of a composite femur under vibration [21], which has ramifications for the design and performance of new orthopedic implants. Other recent works have conducted in-depth investigations into the biomechanics of the femur in fracture fixation and into the phenomena of strain shielding [22,23]. The mechanics of trabecular bone, which is of tremendous interest due to its role in osteoporosis, has been investigated using a novel non-destructive method based on micro-computed tomography technology [24] and was also the subject of a nanoscale biomechanical study by Gao et al [25].…”
Section: Musculoskeletal Biomechanicsmentioning
confidence: 99%